Change management : concepts and practice - Goncalves, Marcus (American Society of Mechanical Engineers, 2007)
Guides us through the do-not's of change management with fatherly wisdom, while masterfully weaving in a constant message: human experience and the synergy in human communication are our most valuable resources. Organizations need to recognize that it is sensitivity to human assets that will allow them to successfully compete in an inevitably changing, fast moving, international business environment. Change Management: Concepts and Practice is a profoundly inspiring guide to setting priorities, effecting change, and good leadership in today's global landscape.
Title from PDF title page (ASME eBooks Web site, viewed 12/04/2010).
Keywords: Organizational change -- Management.; Information technology -- Management.; Knowledge management.; Organizational change.; elektronické knihy; electronic books